1996
DOI: 10.1063/1.472450
|View full text |Cite
|
Sign up to set email alerts
|

Dissociative chemisorption of H2 on Cu(100): A four-dimensional study of the effect of parallel translational motion on the reaction dynamics

Abstract: We investigate the usefulness of a hybrid method for scattering with resonances. Wave packet propagation is used to obtain the time-dependent wave function ⌿(t) up to some time T at which direct scattering is over. Next, ⌿(t) is extrapolated beyond T employing resonance eigenvalues and eigenfunctions obtained in a Lanczos procedure, using ⌿(T) as starting vector to achieve faster convergence. The method is tested on one two-dimensional ͑2D͒ and one four-dimensional ͑4D͒ reactive scattering problem, affected by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 145 publications
3
41
0
Order By: Relevance
“…The domination of vibrational de-excitation by collisions at top sites is consistent with results obtained using a 2D model [9][10][11][12] to examine the scattering of ground state H 2 from Cu͑100͒ which showed that reaction is more likely in collisions with bridge or hollow sites and vibrational excitation occurs primarily at the top site. Specifically, twodimensional calculations 9,10 with the molecular axis held fixed parallel to the surface predict vibrational excitation probabilities of up to 40% for impact at a top site.…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…The domination of vibrational de-excitation by collisions at top sites is consistent with results obtained using a 2D model [9][10][11][12] to examine the scattering of ground state H 2 from Cu͑100͒ which showed that reaction is more likely in collisions with bridge or hollow sites and vibrational excitation occurs primarily at the top site. Specifically, twodimensional calculations 9,10 with the molecular axis held fixed parallel to the surface predict vibrational excitation probabilities of up to 40% for impact at a top site.…”
Section: Resultssupporting
confidence: 86%
“…This independence from collision energy was seen for the average parallel translational energy for molecules incident in the ͑v 0 ϭ0, j 0 ϭ0) state 14 and in 4D calculations in which the molecular orientation was fixed parallel to the surface. 10 This result suggests that energy transfer into parallel translation is not governed by competition with rotational excitation or normal translation but rather by a dynamical restriction on the number of quanta of momentum transferred during a collision. The energy spacing between diffraction states is small so energy transfer into parallel translational motion saturates at low collision energies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The first theoretical [3][4][5][6][7] and experimental [8][9][10][11][12][13][14] studies related to the vibrational enhancement for specific molecule-surface systems were carried out on H 2 dissociation on Cu.…”
Section: Introductionmentioning
confidence: 99%